Sosialisasi Pembuatan Pupuk Organik Cair (POC) Di Lembang Mappa Kecamatan Bonggakaradeng Kabupaten Tana Toraja Dalam Rangka Peningkatan Pendapatan Ekonomi Masyarakat - Althon k.Pongtuluran; Gita Yusuf; Maya Pama’tan; Sernita Panga; Maxsir Maxsir; Efrain Owen Taruk (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
PKM is one part of the learning process that is applied directly in the community. Which focuses on "Agricultural/Fisheries Technology Management" (Manufacture of Liquid Organic Fertilizer (POC)). Lembang Mappa' is one of Lembang whose economy lies in the agricultural and plantation sectors. Almost all residents in Lembang Mappa' work as farmers. There is one problem that has not been resolved, namely how to make organic fertilizer whose ingredients are easily available in Lembang Mappa'. The activity of socializing and making liquid organic fertilizer from gamal leaves, rice washing water, brown sugar or granulated sugar, EM4 was carried out three times with socialization to the public about how to make liquid organic fertilizer and its application to plants. After this activity, it is hoped that farmers will be able to make their own liquid organic fertilizer at home, so they can save money on purchasing fertilizer.